A welfare deservingness approach to the COVID-19 grant: an exploration of the social and economic experiences of unemployed youth in South Africa - Madangatye, Inenceba (Department of Social Development, 2025)
For the longest time, South African youth have not been prioritized in social protection policies (Barford, Coutts, & Sahai, 2021). However, given the current socioeconomic depravations, it can be argued that young people meet the criteria of neediness required to be considered for a permanent welfare policy. The primary objective of this study was to use a welfare deservingness approach to the COVID-19 grant to explore the social and economic experiences of unemployed youth in South Africa. This study used an explorative qualitative research design to gain insight into the attitudes and perceptions that unemployed youth have about receiving the COVID-19 grant. Information was also collected to understand the influence that receiving the COVID-19 relief grant has on the social experiences and economic participation of the youth. Additionally, the purpose of the study was to gauge youth perspectives about continued support in the form of a possible basic income grant. In-depth individual qualitative interviews were conducted with 16 participants who were aged between 21 to 35 years old: at an average age of 25. A subjective or purposive sampling method was used to inform the data collection process, this is a non-probability sampling technique which is useful for gathering qualitative information from a particular population of participants. The study’s findings revealed that youth are desperate for paying job opportunities that can ensure financial stability. Although many of the participants thought the R350 grant money helped in the ways that it could, they also expressed how little this income was in the post-pandemic society. Participants conveyed that the COVID-19 grant does little to alleviate the psychological distress that they feel in response to the dire unemployment crisis. Also, young people expressed their frustrations with the payment delays and system failures associated with the grant. A new comprehensive social protection policy that includes the youth is the recommendation of this study. Based on the findings, this study concluded that young people are struggling to attain certain freedoms, despite the assistance of the COVID-19 grant. Resultantly, it is also recommended that a multidisciplinary approach to welfare deservingness be considered for the youth of South Africa, one which addresses the high unemployment crisis affecting the youth.